Antifungal activity of lactic acid bacteria isolated from fermented catfish (Clarias gariepinus) as biocontrol of sclerotium rolfsii infecting chili plants - Zakaria S.F.; Lani M.N.; Seng C.T.; Ahmad F.; Ahmad K.M.; Hassan Z. (Malaysian Society of Applied Biology, 2024)
Indexed by SCOPUS